Pemikiran Fazlur Rahman dan Muhammad Arkoun - Ajahari, Ajahari (IAIN Palangka Raya, 2016)
Islam is a religion that has a righteous character li wa kulli zamānin makānin. Islam also has a universal doctrine, meaning that applies overall for all nations, place and circumstances. Islam as a religion with a grounding Qur'an and sunnah in certain respects may experience a variety of interpretations and changes in interpretations according to the context of the times, especially in verses mutashabihat and focused on passages that are muamalah, not the verses which is' ubudiyah. For it is necessary that activities remain perpijak ijtihad to the Qur'an and al-Hadith. All modern thinkers assume that if Islam wants to survive and deal with the modern developments, he must undergo a re-definition, re-construction and re-actualization. Among the modern Islamic thinkers who ask these thoughts are Fazlur Rahman Malik and M.Arkoun. Fazlur Rahman Malik asserted that the condition of Muslims will not escape from a variety of problems, difficulties and backwardness unless Muslims back and adhering to the Qur'an. Ignoring a past history does not only imply a denial of the existence of history itself, but also can lead people to lose self-existence and belief systems within the framework of contemporary history.